Identifikasi Minat dan Bakat Olahraga Melalui Metode Sport Search Siswa SMP Negeri 1 Lasem Kabupaten Rembang (Universitas Negeri Semarang, 2021)
Identification of Sports Interests and Talents Through the Sport Search Method in Seventh & Eighth Grade Students in SMP Negeri 1 Lasem, Rembang Regency. Final Project of Department of Physical and Health Education, Universitas Negeri Semarang. This research focuses on the identification of interests and sports talents in sevent and eighth grade students of SMP Negeri 1 Lasem, Rembang Regency on sports. The purpose of this study: To determine the suitability of students' interests and talents in grade VII and VIII of SMP Negeri 1 Lasem, Rembang Regency on sports. The type of this research is quantitative. The survey method of this research used test technique. The research design uses a one-shot case study. Variable research interests and sports talents is in grade VII and VIII students of SMP Negeri 1 Lasem, Rembang Regency with a total sample of 172 seventh and eight grade students . The data collection techniques used test and measurement techniques with the sport search method. Results of this research: VII and VIII grade students' interest in class 5.2% in athletic sports, 18.9% interest in volleyball, 6.5% in martial arts, 19% in futsal, 23.7% in swimming, 0, 6% interest in table tennis, 12.1% interest in basketball, 1.9% in taekwondo, 0.6% in wushu, 5.2% in karate, 0.6% in gymnastics. Students' talents: 22 students (14.1%) volleyball, 1 student (0.6%) badminton, 2 students (1.4%) futsal, 3 students (1.9%) table tennis, 9 students (5.8%) athletic sports, 1 student (0.6%) taekwondo sports. 1 student (0.6%) karate sport, 1 student (0.6%) basketball sport. Suitability of students' interests and talents: 40 students with 25.6% of students' interests and talents are appropriate and 116 students or 74.4% of students' interests and talents are not appropriate. The suggestion given that can be given is the school, both the sports teacher and the sports coach, should pay more attention to the development of students' talents, give the direction to the students and provide adequate facilities, to be more active in directing for talented students who are expected to achieve as much as possible